The Influence of Project Management Knowledge and Leadership Style on the Success of Groundwater Drilling Projects at PT SII - Rofiq, Sholahudin; Silitonga, Roland Y.H.; Heryanto, Dhany (The Indonesian Institute of Science and Technology Research, 2025)
The role of project management knowledge (PMK) and leadership style (LS) is crucial in determining the success of a project. This study aims to identify the influence of PMK and LS on the success of drilling well projects at PT SII (Project Success or PS). The research method used is quantitative, with data analysis conducted using multiple linear regression through SPSS software. Data were obtained through questionnaires distributed to 56 employees involved in drilling well projects. The results show that PMK positively and significantly affects PS. Similarly, LS also positively and significantly impacts PS. These findings suggest that enhancing PMK and adopting effective LS can improve the success rate of projects at PT SII.